Vegetarian Diets and Eating Disorders in Adolescents and Young Adults: A Systematic Review - Theodoros N. Sergentanis; Maria-Eleni Chelmi; Andreas Liampas; Chrysanthi-Maria Yfanti; Eleni Panagouli; Elpis Vlachopapadopoulou; Stefanos Michalacos; Flora Bacopoulou; Theodora Psaltopoulou; Artemis Tsitsika (MDPI AG, 2020)
Background: Eating disorders are more common among adolescents and young adults. An increase in the rates of these disorders has been reported during the last years. Meanwhile, vegetarianism is becoming more popular in these age groups. The purpose of the present paper is to evaluate the association between eating disorders and vegetarian diets in adolescents and young adults. Methods: Systematic review of related articles published in PubMed, PsycInfo and Google Scholar up to 30 May 2019. Results: A total of 20 studies (14,391 subjects) were deemed eligible for this systematic review. The majority of the studies reported significant correlations between vegetarianism and eating disorders. However, due to the cross-sectional design, a causal link between eating disorders and vegetarian status cannot be established. Conclusions: Vegetarianism seems to be associated with eating disorders. Longitudinal studies are needed to establish temporal patterns between vegetarianism and the emergence of disordered eating.